“A PhD is just going to somehow break you”: A qualitative study exploring the role of peer support for doctoral students - Fiona Newlands; Tanvi Markan; Isabelle Pomfret; Emily Davey; Tom King; Anna Roach; Millie Wagstaff; Tom G. Osborn; Roz Shafran; Polly Livermore; Michelle de Haan; Jeanne Wolstencroft; et al. (PLoS ONE, 2025)
Doctoral (PhD) students experience high rates of mental health challenges, including high rates of anxiety, depression, loneliness, and isolation. While universities offer mental health services, these may not fully address the specific needs of doctoral students. Peer support has emerged as a promising adjunct to existing service provision, drawing on shared experiences to provide emotional and practical guidance. This study aimed to explore doctoral students’ perceptions of peer support, identifying their needs and preferences for a peer support programme tailored to the doctoral experience. Nineteen doctoral students were recruited from a university in the south of England and participated in focus groups or semi-structured interviews. Thematic analysis yielded four overarching themes: (1) Barriers to seeking support; (2) Value of peer support for doctoral students; (3) Tailored peer support needs; and (4) Diversity and accessibility. Findings indicate that doctoral students value peer support as a flexible, informal space to share experiences and gain advice from those with similar backgrounds. However, they also emphasised the need for diverse representation among peer supporters, adaptable training to meet neurodiverse needs, and formal recognition of peer supporters’ contributions. Study findings suggest that universities should consider implementing tailored peer support programmes to address the specific challenges faced by doctoral students, incorporating flexibility, cultural sensitivity, and accessibility to create a supportive academic environment. Future research should evaluate the effectiveness of such programs in improving doctoral students’ mental health and well-being.